Smart Card Berbantuan Wordwall Materi Ekosistem Melalui PBL Meningkatkan Adversity Quotient Kelas V SD - Oktriananda, Kana; Fatih , Mohamad; Wafa, Khoirul (Papanda Publisher, 2025)
This research aims to develop a Wordwall-assisted Smart Card with a focus on ecosystem material, as well as increasing students' Adversity Quotient. In addition, this research also aims to test the effect of using Smart Cards assisted by Wordwall on Adversity Quotient abilities in grade V elementary school students. The approach used in this research is Research and Development (R&D), following the development steps proposed by Borg and Gall. The results of validation from media experts showed a score of 95%, while validation from material experts obtained a score of 94%. Both results are included in the